REGENERASI TOPENG RANDEGAN - Ria Intani (Patanjala: Journal of Historical and Cultural Research, 2016)
Topeng Randegan is one of the types of art that developed in the village of Randegan, both West and East Randegan, Jatitujuh District, Majalengka Regency. Topeng Randegan in the village of East Randegan is "a continuation" of the topeng beber that develops the village of Beber, Ligung District, Majalengka regency. The research on this art is to know how the regeneration of the TopengRandegan. In case that there is only one maestro of Topeng Randegan in Randegan East Village and have entered the old age, so it is assumed that Topeng Randegan is endangered.  This study uses qualitative method and the research findings are outlined descriptively. The results show that there is only one studio that develops Topeng Randegan. Thus,Topeng Randegan attempts to sustainability, and passes on to the younger generation through non-formal education (courses). But, it is unfortunate that the learners come only in short-term period. They learn dance Topeng Randegan not for a purpose or goal as a dance artist, caused by school work. Therefore, the learning process is instant, andthe result is only for performing.